Cardiovascular risk perception among adults in a rural population of Malaysia / Nazar Mohd Zabadi Mohd Azahar - Mohd Azahar, Nazar Mohd Zabadi (2013)
Risk perception is an important component which would bring about changes in unhealthy lifestyle. Underestimation of risk would reduce the commitment of individuals from making a significant change in their lifestyle including dietary habits,activity levels, and tobacco usage to decrease their risk for CVD. The objectives of this study are (i) To determine the proportion of cardiovascular risk factors in the studied population, (ii) To determine the Framingham Risk Score in the studied population, (iii) To determine the association between cardiovascular risk perception with socio-demographic characteristics, (iv) To determine the level of cardiovascular risk perception with respect to cardiovascular risk factors and (v) To determine the association between cardiovascular risk perception with Framingham risk scores. This cross-sectional study was conducted between July 2010 to June 2011 in Raub,Malaysia involving adults aged 30 years and above. Sampling of subjects was done based on purposive convenient sampling. Blood pressure measurement was taken twice and an average was recorded. Anthropometric measurement was done for BMI and WHR determination. Venous blood samples were obtained for Fasting Blood Glucose and Fasting Serum Lipid Assays. Framingham Risk Score was calculated using the “General Cardiovascular Risk Profile for Use in Primary Care: The Framingham Heart Study online calculator”. A set of modified Risk and Health Behaviours Questionnaire was used to measure the cardiovascular risk perception scores. Prior to the study, a pilot study was done to evaluate the reliability of the questionnaire. The Cronbach’s alpha was 0.972 for this questionnaire. A total of 600 rural respondents (meaniSD of age: 59.5±10.7 years; 41.7% males) participated in this study. A majority were married (80.9%), had primary education (64.8%), housewives (44.3%) and had a monthly household income of RM501-RM1500 (57.9%). The proportion with hypertension was 63.8%, smoking was 14.3%, obesity was 30.2%, elevated WHR was 77.1%, diabetes was 23.7% and dyslipidemia was 83.7%. Based on Framingham risk score, 42.4% of the respondents were at high risk for cardiovascular diseases (CVD) in the next 10 years. A majority of males (63.2%) were at high risk for CVD while 44.5% of females were in the low risk group.Cardiovascular risk perception scores were found to be significantly negatively correlated with age (r=-0.097, p=0.018) and waist hip ratio (r=-0.098, p=0.017).Monthly household income of the respondents was significantly associated with the cardiovascular risk perception scores (F(3,573)=l 0.649, p<0.001). Hypertensives who took anti-hypertensive medications had significantly higher cardiovascular risk perception scores (t(371)=2.110, p=0.036). Hypertensives who were aware of their hypertension had significantly higher cardiovascular risk perception score (t(361)=2.189, p=0.029). Among respondents who were on anti-hypertensive medications and successful in controlling their blood pressure had significantly higher cardiovascular risk perception score (t(171)=2.640, p=0.009). Framingham Risk Score was found to be significantly associated with cardiovascular risk perception score (F(2,433)=3.352, p=0.036). Almost half of the rural respondents had high risk for developing CVD. Increasing age, low monthly household income, elevated WHR,hypertensive who were not on treatment, unaware of their hypertension status and unsuccessful in controlling their blood pressure had low cardiovascular risk perception. Framingham Risk Score was significantly associated with cardiovascular risk perception score. Healthcare providers should develop relevant strategies to improve the cardiovascular risk perception among the rural population to augment better control of CVD risk factors.